Challenges in Renewable Energy Supply Chains: Strategies for a Sustainable Energy Future Authors - Rahman, Saleem ur; Shakeel, Shah Rukh (Springer, 2025)
Mitigating climate change is one of the most pressing issues today. A key step in addressing climate change is reducing reliance on fossil fuels, which requires a global shift toward renewable energy. However, this transition faces numerous supply chain challenges, including unpredictable resource availability, financial limitations, regional political instability, technological gaps, social and environmental impacts, and inconsistent regulations and policies. These challenges lead to production delays, power interruptions, decreased energy efficiency, and disruption of the smooth flow of materials, slowing the global adoption of renewable energy technologies. This chapter addresses these critical challenges in the renewable energy sector. The findings indicate that geographical, technological, geopolitical, infrastructural, social and environmental, financial, regulatory, and governmental challenges significantly affect the entire supply chain, from extraction to the production of renewable energy technologies between technology-rich and resource-rich countries. The chapter also suggests future trends for overcoming supply chain disruptions and fostering greater cooperation, innovation, and sustainability in transitioning to a renewable energy-based future.
Keywords: Renewable Energy; Supply chain; Challenges; Energy transition; Sustainability; Marketing; Markkinointi